Ficedula hypoleuca subsp. tomensis Johansen 1916 ... - Salvador, Rodrigo B.; Jeugd, Henk Van Der; Tomotani, Barbara M. (Zenodo, 2017)
F. h. tomensis (Johansen, 1916) Muscicapa atricapilla tomensis Johansen, 1916: 101 [new name for Muscicapa atricapilla sibirica Khakhlov, 1915]. Type locality and material: as for sibirica (see above). The name tomensis Johansen, 1916 is a replacement name for sibirica Khakhlov, 1915, the latter having been published in Muscicapa where it is a junior primary homonym of Muscicapa sibirica Gmelin, 1789 and so permanently invalid (Article 57.2 of the Code). This subspecies is considered to be clearly diagnosable from nominate hypoleuca (e.g., Johansen 1954), although the location of and circumstances in their contact Zone is poorly understood. It occurs in the taiga of west Siberia, from the Ural Mountains to the Yenisey River, wintering in east Africa (Clements et al. 2015). ... : Published as part of Salvador, Rodrigo B., Jeugd, Henk Van Der & Tomotani, Barbara M., 2017, Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae), pp. 171-182 in Zootaxa 4291 (1) on page 175, DOI: 10.11646/zootaxa.4291.1.10, http://zenodo.org/record/829327 ...